After 10 years, how do changes in asset ownership affect the Indicador Econômico Nacional? - Fernanda Ewerling; Aluísio J D Barros
ABSTRACT OBJECTIVE Our main objective was to analyse how the evolution of household assets ownership affected the Indicador Econômico Nacional (IEN - National Wealth index) and to point out the most stable assets and which lost importance more quickly. METHODS We analysed the trend of the ownership of each IEN variable and the distribution of the households' scores. We calculated the correlation coefficients of each variable separately with the IEN score and the household income. We also evaluated how the changes of the score distribution over time affected the validity of the published reference cut-points. We used data from consortium surveys conducted every two years from 2002 to 2014 in the city of Pelotas, Brazil. RESULTS An increase in the educational level of household heads and in the ownership of all IEN assets, except radio and telephone, was observed in the study period. In general, the correlation of the assets with the IEN scores decreased over time. There was an increase in the score, with a consequent increase in the quintiles cut-points, but the distance between these cut-points had no significant variation. Thus, the reference cut-points for Pelotas, quickly became outdated. CONCLUSIONS Some assets showed greatly reduction on its importance for the indicator, and the reference cut-points became obsolete very quickly. It is essential for a standardized wealth (or asset) index with research purposes to be updated frequently, especially the cut-points of reference distribution.